Toughening of PP/EPDM blend by compatibilization - Kim, BC; Hwang, SS; Lim, KY; Yoon, KY (JOHN WILEY & SONS INC, 2000)
To improve the mechanical properties of blends of polypropylene (PP) and terpolymer of ethylene-propylene-diene, (EPDM), a triblock copolymer, (PP-g-MAH)-co-[PA-6,6]-co-(EPDM-g-MAH), was synthesized by coupling reaction of maleic anhydride (MAH)-grafted PP (PP-g-MAH), EPDM-g-MAH, and PA-6,6. The newly prepared block copolymer brought about a physical interlocking between the blend components, and imparted a compatibilizing effect to the blends. Introducing the block copolymer to the blends up to 5 wt % lead to formation of a beta-form crystal. The wide-angle X-ray diffractograms measured in the region of 2 theta between 10 degrees and 50 degrees ascertained that incorporating the block copolymer gave a new peak at 2 theta = 15.8 degrees. The new peak was assigned to the (300) plane spacings of the beta-hexagonal crystal structure. In addition, the block copolymer notably improved the low-temperature impact property of the PP/EPDM blends. The optimum usage level of the compatibilizer proved to be 0.5 wt %. (C) 2000 John Wiley & Sons, Inc.
Keywords: POLYPROPYLENE; RUBBER; MORPHOLOGY; POLYAMIDE-6